Threats To Food Security in The Food and Energi Barn Area: Agricultural Land Function Change in Bojonegoro Regency - Agus Danugroho (ARISTO, 2022)
This study aims to analyze how the threat of food security is due to the conversion of agricultural land in Bojonegoro Regency, which is used as an oil and gas industry. As we know, the slogan of Bojonegoro Regency is the Food and Energy Barn. However, this slogan also raises the question of whether the two aspects of food and energy can be balanced or if they will only harm one another. This study uses a descriptive qualitative method supported by data to strengthen the author's argument. The results of this study state that the slogan of the Bojonegoro Regency with Food and Energy Barns is a questionable thing in reality. Districts with abundant natural wealth of oil and gas pose a threat to food security due to the many shifts in the function of agricultural land. The impact of the conversion of agricultural land in several villages also causes various economic and environmental impacts. The Bojonegoro Regency Government needs to review and think about strategies to manage and make the Bojonegoro Regency slogans real and have an impact on the surrounding community. Researchers provide policy recommendations with balanced management between the oil and gas and food sectors for the sake of realizing it as a District of Food and Energy Barns.